Evaluation of Rengginang MSME Production Performance with the Implementation of Quality Function Deployment (QFD) - Irawan, Suhendi; Adisty, Revinia; Dardanella, Derry; Indrawan, Purana; Risyahadi, Sazli Tutur; Wijaya, Hendri; Kartinawati, Annisa; Apriliani, Fany (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study aims to evaluate the production performance of Micro, Small, and Medium Enterprises (MSMEs) in rengginang production using the Quality Function Deployment (QFD) approach. Rengginang is a traditional Indonesian snack made from sticky rice, which has economic and cultural value but faces challenges in production consistency, hygiene, and capacity due to manual processing methods. The QFD method was applied to translate six key customer needs—such as production speed, hygiene, capacity, consistency, quality control, and product variation flexibility—into technical characteristics through the House of Quality (HoQ) matrix. Results showed that the most critical production need was achieving a drying process of no more than one day, followed by hygienic handling. These were translated into technical priorities such as high-speed drying machines and closed-drying systems. The relative weight analysis indicated that these technical improvements had a high impact on production performance with relatively moderate implementation complexity. This study provides MSME actors with a structured model to improve production efficiency and competitiveness based on customer-oriented planning. Keywords: Quality Function Deployment (QFD), House of Quality, MSMEs, Rengginang, Production Performance